Playing Through : African American Baseball in Dunn County, Wisconsin - Carter, Matthew C. (My University, 2012)
This study looked at African American history in Dunn County, Wisconsin, through the context of barnstorming baseball.
Color poster with text and images.
Keywords: African American baseball players--Wisconsin--Dunn County--History; Dunn County (Wis.)--History; Posters